Co-constructing or Deconstructing Gender Identity? A Multimodal Critical Discourse Analysis of Bongo Flava- Song Video Niambie - Musa Saimon (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Abstrak. Musik seperti media lain memberikan semacam wacana yang aspek sosial seperti identitas gender dari masyarakat terkait dapat bersama-sama dibangun atau didekonstruksi tergantung pada perspektif ideologis pembicara/penulis. Penelitian ini menganalisis Bongo Flava-Song video ' Niambie ' menggunakan perspektif wacana kritis multimodal sehingga untuk memeriksa apakah lagu melibatkan Co-konstruksi atau dekonstruksi identitas gender. Hasil menunjukkan bahwa identitas gender dalam video lagu dikonstruksi bersama dalam arti bahwa gender pria dominan dibandingkan gender wanita yang menyinggung dari ideologi patriarki yang melaluinya manusia seharusnya mendominasi wanita dalam semua aspek kehidupan. Kata kunci: identitas gender, analisis wacana kritis multimodal, Bongo FlavaAbstract. Music like any other media provides a kind of discourse through which social aspects like gender identity of a particular related society can be co-constructed or deconstructed depending on the ideological perspective of the speaker/writer. This paper analyses Bongo Flava-song video ‘Niambie’ using multimodal critical discourse perspective so as to examine if the song involves co-construction or deconstruction of gender identity. Results show that gender identity in the song video is co-constructed in the sense that male gender is dominant over female gender alluding from patriarchal ideology through which men are supposed to dominate women in all life aspects. Keywords: Gender identity, Multimodal critical discourse analysis, Bongo Flava